2021
DOI: 10.3390/en14216928
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt to Use Machine Learning Algorithms to Estimate the Rockburst Hazard in Underground Excavations of Hard Coal Mine

Abstract: Rockburst is a dynamic rock mass failure occurring during underground mining under unfavorable stress conditions. The rockburst phenomenon concerns openings in different rocks and is generally correlated with high stress in the rock mass. As a result of rockburst, underground excavations lose their functionality, the infrastructure is damaged, and the working conditions become unsafe. Assessing rockburst hazards in underground excavations becomes particularly important with the increasing mining depth and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The ANN in Ulivieri’s study showed good discrimination, with an AUC of 0.8 by external validation 40 . Machine learning approaches were also applied to develop geological prediction models which provided the triage solutions to predict an occurance of rockburst during underground rock excavations 41 , 42 . We also figured out that the averaged AUROC values of the four tools in our study were higher than ones of FRAX models which were calculated at 0.796 and 0.768 respectively 43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ANN in Ulivieri’s study showed good discrimination, with an AUC of 0.8 by external validation 40 . Machine learning approaches were also applied to develop geological prediction models which provided the triage solutions to predict an occurance of rockburst during underground rock excavations 41 , 42 . We also figured out that the averaged AUROC values of the four tools in our study were higher than ones of FRAX models which were calculated at 0.796 and 0.768 respectively 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to our methods, the indices (precision, recall, F1-core) were estimated to evaluate the performance of machine learning algorithms 41 , 42 . Ullah et al developed Extreme Gradient Boosting (XGBoost) model with support from K-means clustering and an enhanced stochastic neighbour embedding (SNE) Based t-SNE algorithm to predict the risk of rockburst 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the deep mining of coal seam, the problems of coal-rock dynamic disaster prevention and control such as rockburst have been paid more attention. In this context, researchers have studied various problems arising in the process of rockburst, for example, the internal or external causes of rockburst, , the risk assessment of rockburst accident, the law of coal-rock cracking, the law of impact signal transmission, etc. In these research fields, coal-rock dynamic disaster prediction plays an important role, which is directly related to the safety of life and property.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rapid development of China's economy, large quantities of coal resources in shallow mining have been basically depleted, so the mining of most coal resources has moved to the deep-lying stratum [1][2][3]. With the increase in the mining depth, both the frequency and intensity of the coal mining engineering risk in the underground stope are increasing, such as rock burst, soft rock large deformation, water inrush and flowing deformation [4][5][6], which brings tremendous threat to the efficient mining of coal resources and the safety of miners. For the deep soft rock mining roadway, the structural instability and nonlinear large deformation of surrounding rock are the most common problems with the stress environment's deterioration [7].…”
Section: Introductionmentioning
confidence: 99%